Modification method of colocasia esculenta peel dietary fiber
Patent Information
- Application Number
- CN202611043270.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-11-03
AI Technical Summary
Existing dietary fiber modification processes rely on exogenous chemical reagents, making it difficult to balance the modification effect with the utilization efficiency of all by-product components, and also posing risks of reagent residue and loss of active components.
A low-eutectic solvent was prepared by using endogenous components from taro peel. Combined with low-temperature steam flash explosion, closed endogenous acid aging activation, dual-frequency ultrasonic treatment, and continuous wet transfer process, fiber structure modification and in-situ utilization of active components were achieved, avoiding the addition of exogenous reagents.
This method achieves green and clean dietary fiber modification, improves the efficiency of full-component resource utilization of by-products, and maintains the balance of modification effects and the safety of the product for consumption.
Smart Images

Figure CN123023732A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of food processing technology, and more specifically, it relates to a method for modifying the dietary fiber in the peel of taro. Background Technology
[0002] Taro is a specialty tuber crop widely cultivated in southern my country. During the processing of taro paste, frozen taro chunks, and other foods, a large amount of taro peel byproducts are generated. These byproducts are rich in dietary fiber and natural active components such as polyphenols and polysaccharides, possessing high resource utilization value. The functional properties of dietary fiber are directly related to its structural state. To improve the physicochemical properties and application value of dietary fiber, it is usually necessary to modify it. Eutectic solvent modification, as a mild and green modification technology, has been gradually applied in the field of dietary fiber structural modification.
[0003] Currently, in the technologies related to dietary fiber modification using eutectic solvents, the modifying solvents are mostly formulated from purchased chemical raw materials. The overall process relies on the addition of exogenous chemical reagents, which increases the cost of raw materials and poses a certain risk of reagent residue. At the same time, existing processes usually separate and remove the endogenous active components contained in the raw materials as impurities, making it impossible to achieve the synergistic utilization of all components of the by-product raw materials. It is difficult to ensure the modification effect while taking into account the food safety of the product and the resource utilization efficiency of the by-products. Summary of the Invention
[0004] To address the problems in existing dietary fiber modification processes that rely on exogenous chemical reagents and struggle to balance modification effectiveness with the overall utilization efficiency of byproducts, this application provides a method for modifying dietary fiber from taro peel.
[0005] A method for modifying dietary fiber in taro peel, comprising the following steps: S1. Raw material pretreatment: Take fresh taro peel, wash and remove impurities, and then process it through hot air drying, crushing and sieving to collect taro peel dry powder. S2. Steam flash explosion hole making: After adjusting the moisture content of taro peel powder, let it stand and soak, then steam explosion treatment, keep it at constant temperature and pressure, and then instantly release the pressure to normal pressure. S3, acid aging and activation treatment: After depressurization, the reaction system is kept in a closed state, and the residual heat of the material is used to maintain the system temperature for aging treatment. After aging, the activated material is discharged. S4. Solvent intercalation and deconstruction: The activated material is added to a pre-prepared endogenous eutectic solvent, the mass-volume ratio of the material and the mixture is controlled, and the mixture is stirred at a constant temperature. S5. Ultrasonic structural reconstruction: The material processed in step S4, together with the solvent system, is placed in an ultrasonic field and ultrasonically treated under constant temperature conditions. The ultrasonic treatment adopts a method of alternating low-frequency and high-frequency ultrasound. Low-frequency ultrasound and high-frequency ultrasound are applied sequentially in each working cycle, with an interval between working cycles. S6. Polysaccharide pore-stabilizing passivation: After ultrasonic treatment, homologous taro peel endogenous polysaccharide is added to the reaction system and stirred at a constant temperature. S7. Separation and drying sample preparation: Add deionized water to the reaction system for dilution, collect the precipitate by centrifugation, wash the precipitate until the eluent is neutral, and obtain the modified taro peel dietary fiber product after freeze drying.
[0006] By adopting the above technical solution, a eutectic solvent prepared from the endogenous components extracted from the raw materials is used as the core modification medium. Combined with a multi-step progressive modification process, the entire process of fiber pore formation, pre-activation, crystallization zone deconstruction, structural reconstruction and pore stabilization is completed in sequence. There is no need to introduce a large amount of exogenous chemical reagents. At the same time, the in-situ utilization of the endogenous active components of the raw materials can be realized simultaneously. The overall process is green and clean, the modification effect is balanced, and the resource utilization efficiency of the by-products can be improved.
[0007] Preferably, in step S1, the temperature of the hot air drying is 50 to 60°C, the cross-sectional wind speed is 1.0 to 2.0 m / s, the taro skin is cut into small pieces of 2 to 5 cm before drying, and the moisture content of the material after drying is less than 10%; the crushing adopts a two-stage process of coarse crushing and fine crushing, and the sieve mesh number is 40 to 60 mesh.
[0008] By adopting the above technical solution, the raw materials are pre-cut into uniform sizes and then graded, dried and pulverized. This ensures that the materials are heated and stressed evenly, avoids local over-drying or uneven particle size, and the mild drying conditions can reduce the degradation of heat-sensitive active components in the raw materials. The uniformly sized dry powder can provide a stable and consistent reaction base for subsequent reaction steps, improving the uniformity of the overall modification treatment.
[0009] Preferably, in step S2, the moisture content is 25% to 30%, and the static soaking time is 15 to 25 minutes; the constant temperature and pressure insulation temperature is 110 to 120°C, the pressure is 0.15 to 0.20 MPa, and the insulation time is 3 to 5 minutes; the steam pressure rise rate is 0.02 to 0.05 MPa / s, and the total duration of instantaneous pressure relief is 0.1 to 0.5 seconds.
[0010] By adopting the above technical solution, the moisture content of the material is first controlled and then steam explosion treatment is carried out. The gentle pressurization process can avoid local heat damage to the material. The mild temperature and pressure conditions can form cracks and channels inside the fiber and loosen the fiber aggregate structure, while greatly reducing the damage of high temperature to active components. The impact force formed by instantaneous pressure relief can further break the dense fiber structure and provide sufficient channels for the deep penetration of the subsequent modified medium.
[0011] Preferably, in step S3, the temperature of the simmering treatment is 90 to 100°C, and the treatment time is 10 to 15 minutes; during the simmering process, the reaction system is maintained under a slightly positive pressure, with a gauge pressure of 0.01 to 0.03 MPa; after the simmering is completed, the pressure is first slowly released to atmospheric pressure, and then the material is discharged.
[0012] By adopting the above technical solution, the residual heat of the material is used for simmering in a closed environment. The slightly positive pressure state can enhance the penetration depth of the endogenous organic acids released by flash explosion into the fiber interior, gently loosen the amorphous structure of the fiber and introduce more active reaction sites. After simmering, the pressure is slowly released to avoid fiber pore shrinkage and collapse caused by sudden pressure changes, maintain the formed loose structure, and provide a good foundation for subsequent solvent intercalation treatment.
[0013] Preferably, in step S4, the endogenous eutectic solvent is prepared using citric acid and taro polysaccharide extracted from taro peel as hydrogen bond donors and choline chloride as hydrogen bond acceptor; the molar ratio of citric acid, taro polysaccharide and choline chloride is 1:0.4 to 0.6:0.2 to 0.4; the preparation process involves mixing the three components, stirring at a constant temperature of 75 to 85°C until a homogeneous and transparent liquid is formed, and then cooling to room temperature before use.
[0014] By adopting the above technical solution, citric acid and taro polysaccharide extracted from taro peel are used as hydrogen bond donors and hydrogen bond acceptors to prepare a low eutectic solvent. The endogenous components have a stronger structural compatibility with the fiber matrix. They can be inserted into the cellulose crystal region through strong hydrogen bonding, breaking the intermolecular hydrogen bond network and gently deconstructing the fiber crystal structure. During the process, endogenous polyphenolic substances bound to the fiber can also be dissolved simultaneously, providing in-situ reaction substrates for subsequent functionalization modification.
[0015] Preferably, in step S4, the mass-to-volume ratio of the material to the liquid is 1:15 to 1:20, the temperature of the constant-temperature stirring is 50 to 60°C, the rotation speed is 180 to 220 r / min, and the processing time is 40 to 60 min; the entire process is carried out under light-protected conditions.
[0016] By adopting the above technical solutions, the appropriate material-liquid ratio and stirring conditions can ensure that the materials are fully dispersed in the solvent system, avoid local agglomeration, promote the continuous diffusion and mass transfer of the modified medium into the fiber interior, ensure the efficiency of intercalation and deconstruction, and the light-proof treatment conditions can reduce the oxidative loss of endogenous polyphenols and other photosensitive active components, and maintain the functional activity of endogenous active substances.
[0017] Preferably, in step S5, the power density of the ultrasonic treatment is 200 to 300 W / L, and an alternating operation mode of 2 seconds working and 3 seconds intermittent is adopted; in each working cycle, low-frequency ultrasound with a frequency of 20 kHz is applied in the first 1 second, and high-frequency ultrasound with a frequency of 80 kHz is applied in the last 1 second; the temperature of the constant temperature treatment is 45 to 55°C, and the treatment time is 20 to 30 minutes; a circulating water bath is used for temperature control during the ultrasonic treatment.
[0018] By adopting the above technical solution, the alternating operation mode of continuous and intermittent operation can avoid local overheating of the system and excessive degradation of fibers caused by continuous ultrasound. Ultrasound of different frequencies plays a role in time division. The strong cavitation effect of the low frequency band can further expand the fiber pores and refine the fiber segments, while the high frequency band can promote the movement and rearrangement of cellulose molecular chains and increase the collision probability between active components and fiber reaction sites. With stable temperature control conditions, the construction of the three-dimensional network structure of the fiber and the in-situ immobilization of the endogenous active components can be realized simultaneously.
[0019] Preferably, in step S6, the added endogenous polysaccharide and the taro polysaccharide used to prepare the eutectic solvent are homologous extraction components, and the amount added accounts for 1% to 2% of the total mass of the system; the constant temperature stirring temperature is 48 to 52°C, the rotation speed is 120 to 180 r / min, and the processing time is 5 to 8 min.
[0020] By adopting the above technical solution, endogenous polysaccharides that are homologous to the solvent components are used, resulting in better compatibility with the entire reaction system. After addition, they can quench trace amounts of residual free radicals in the system, precisely terminating the grafting reaction process induced by ultrasound. At the same time, polysaccharide molecules can be adsorbed on the edge of fiber pores, forming a steric hindrance effect, inhibiting the hydrogen bond rearrangement and aggregation of fiber molecular chains during subsequent drying, stabilizing the constructed porous structure, and ensuring the stability of the product's adsorption performance.
[0021] Preferably, in step S7, the volume of deionized water added is 3 to 5 times the volume of the reaction system; the centrifugation speed is 3500 to 4500 r / min, and the centrifugation time is 8 to 12 min; the cold trap temperature for freeze drying is -50 to -40°C, and the drying time is 20 to 28 h.
[0022] By adopting the above technical solution, after adding deionized water to dilute the reaction system and then centrifuging and washing, the solvent and small molecule impurities attached to the fiber precipitate can be fully removed, ensuring product purity. The water is removed by freeze drying, which can be completed in a low-temperature vacuum environment, avoiding fiber pore collapse, structural shrinkage and degradation of active components caused by conventional high-temperature drying, and preserving the porous structure and biological activity of the modified fiber to the greatest extent.
[0023] Preferably, in steps S2 to S6, between two adjacent steps, the material obtained in the previous step is used directly as the feed for the next step without being dried or washed.
[0024] By adopting the above technical solution, materials can be directly transferred between adjacent processes without washing and drying, eliminating multiple intermediate processing steps. This reduces the overall energy consumption and wastewater generation of the process. At the same time, it avoids fiber hydrogen bond rearrangement, pore structure collapse and loss of endogenous active components caused by intermediate drying process, maintains the wet and dispersed state of materials, ensures the continuity of modification effects of each step, and improves the overall modification efficiency and product performance.
[0025] In summary, this application has the following beneficial effects: 1. Because this application adopts a whole-chain modification process with the endogenous components of taro peel as the core, it relies on the eutectic solvent prepared by the endogenously extracted citric acid and taro polysaccharide to complete the deep deconstruction of the fiber crystallization zone. Combined with multiple consecutive processes, it realizes the in-situ utilization of structural modification and active components. It does not require the addition of a large amount of exogenous chemical reagents, and obtains a green, clean and balanced modification effect. At the same time, it realizes the high-value utilization of all components of processing by-products.
[0026] 2. In this application, a pretreatment method of low-temperature and low-pressure steam flash explosion combined with closed endogenous acid quenching is preferred. Since the flash explosion process creates cracks and channels inside the fiber to provide channels for organic acid penetration, the endogenous organic acid quenching stage completes the fiber preactivation by means of the material itself, without the need to introduce additional acidic reagents. This achieves both moderate loosening of the fiber structure and reduction of heat-sensitive active component loss caused by high-temperature treatment, thus achieving a balance between pretreatment efficiency and activity retention.
[0027] 3. The method of this application adopts an alternating treatment mode of low-frequency ultrasound and high-frequency ultrasound. The low-frequency ultrasound enhances the expansion of fiber pores and the refinement of segments, while the high-frequency ultrasound promotes molecular chain rearrangement and collision grafting of active components. The two work together in a time-sharing manner, which breaks through the functional limitation of single-frequency ultrasound that can only assist in degradation. Therefore, the effect of simultaneous completion of fiber structure modification and functional modification is achieved.
[0028] 4. In this application, a continuous wet process without intermediate washing and drying between processes is preferred. Combined with the endogenous polysaccharide pore-stabilizing passivation step after ultrasonic treatment, the fiber hydrogen bond rearrangement and pore collapse caused by intermediate drying are avoided. The polysaccharide molecules can form steric hindrance at the pore edge to maintain the porous structure, thus achieving the effect of stable modified fiber structure and long-term maintenance of product performance. Attached Figure Description
[0029] Figure 1 This is a flowchart of a method for modifying dietary fiber in the peel of taro, as provided in this application; Figure 2 This is a comparison chart of the water-holding capacity and oil-holding capacity test results of the various embodiments and comparative examples provided in this application; Figure 3 This is a comparison chart of the DPPH free radical scavenging rate measurement results of the various embodiments and comparative examples provided in this application. Detailed Implementation
[0030] The present application will be further described in detail below with reference to embodiments and comparative examples. Unless otherwise specified, the experimental methods used below are conventional methods. Unless otherwise specified, the materials, reagents, methods and instruments used are all conventional materials, reagents, methods and instruments in the art, which can be obtained by those skilled in the art through commercial channels or prepared according to literature methods.
[0031] Technical Concept: Current technologies for modifying dietary fiber from taro peel generally use exogenous chemical reagents or commercial enzyme preparations as the core modification medium. The endogenous components naturally present in the raw materials, such as citric acid and plant polysaccharides, are mostly treated as impurities and removed, failing to be converted into modified functional components to participate in the reaction. Furthermore, existing processes lack mechanistic coordination between pretreatment and deep modification steps, with independent washing and drying stages often occurring between processes. This easily leads to fiber structure shrinkage and collapse, as well as the loss of endogenous active components, making it difficult to simultaneously achieve both the depth of fiber modification and the full utilization efficiency of byproducts under green and gentle processing conditions.
[0032] This scheme revolves around the core idea of synergistic utilization of endogenous components. It uses citric acid extracted from taro peel and taro polysaccharides to prepare a eutectic modification solvent. The fiber pre-loosening is completed by low-temperature steam flash explosion pore creation combined with closed endogenous acid simmering activation. Then, the three-dimensional structure reconstruction of the fiber and the in-situ immobilization of endogenous polyphenols are achieved simultaneously by the time-division action of dual-frequency alternating ultrasound. Finally, the reaction is terminated and the pores are stabilized by homologous endogenous polysaccharides. The entire process adopts a continuous wet transfer process to build a complete endogenous closed-loop modification system, which reduces the dependence on exogenous reagents while improving the overall modification effect and resource utilization rate.
[0033] Example 1: This example provides a method for modifying dietary fiber from taro peel, the specific process of which is as follows: S1. Raw material pretreatment: Take fresh taro peel, wash and remove impurities, and then process it through hot air drying, crushing and sieving to obtain taro peel dry powder.
[0034] Before drying, the taro skin is cut into 3.5cm pieces. The hot air drying temperature is 55℃ and the cross-sectional wind speed is 1.5m / s. After drying, the moisture content of the material is controlled at 8%. The crushing process adopts a two-stage process of coarse crushing and fine crushing. After fine crushing, the sieve mesh size is 50 mesh.
[0035] S2. Steam flash explosion hole making: After adjusting the moisture content of taro peel powder, let it stand and soak, then perform steam explosion treatment, keep it at constant temperature and pressure, and then instantly release the pressure to normal pressure.
[0036] The adjusted material moisture content was 27.5%, and the static soaking time was 20 minutes; the steam pressurization rate was 0.035 MPa / s; the constant temperature and pressure holding temperature was 115℃, the pressure was 0.175 MPa, and the holding time was 4 minutes; the total instantaneous pressure relief time was 0.3 seconds. The material processed in this step was directly introduced into the next step without drying or washing.
[0037] S3, Acid Activation Treatment: After depressurization, the reaction system is kept in a closed state, and the residual heat of the material is used to maintain the system temperature for activation treatment. After activation, the activated material is discharged.
[0038] The annealing process involves a temperature of 95℃ and a treatment time of 12.5 minutes. During annealing, the reaction system is maintained under a slight positive pressure, with a gauge pressure of 0.02 MPa. After annealing, the pressure is slowly released to atmospheric pressure before the material is discharged. This process utilizes the endogenous organic acids released from the material to gently loosen the surface structure of the fibers, increasing the number of active reaction sites. The activated material processed in this step is not dried or washed and proceeds directly to the next step.
[0039] S4. Solvent intercalation and deconstruction: The activated material is added to a pre-prepared endogenous eutectic solvent, the mass-volume ratio of the liquid is controlled, and the mixture is stirred at a constant temperature.
[0040] The endogenous eutectic solvent was prepared using citric acid and taro polysaccharide extracted from taro peel as hydrogen bond donors and choline chloride as hydrogen bond acceptor. The molar ratio of citric acid, taro polysaccharide, and choline chloride was 1:0.5:0.3. The preparation process involved mixing the three components and stirring at a constant temperature of 80°C until a homogeneous and transparent liquid was formed. The mixture was then cooled to room temperature before use. In this embodiment, the taro polysaccharide was obtained from taro peel and prepared using hot water extraction and ethanol precipitation. It is a water-soluble plant polysaccharide, and its molar amount was calculated based on monosaccharide residue equivalents. The material-to-liquid mass-to-volume ratio was 1:17.5. The constant temperature stirring temperature was 55°C, the stirring speed was 200 r / min, and the processing time was 50 min. The entire process was conducted under light-protected conditions to reduce the oxidative loss of endogenous active components. The material and solvent system processed in this step were directly introduced into the next step without drying or washing.
[0041] S5. Ultrasonic structural reconstruction: The material processed in step S4, together with the solvent system, is placed in an ultrasonic field and ultrasonically treated under constant temperature conditions. The ultrasonic treatment adopts an alternating operation of low-frequency ultrasound and high-frequency ultrasound. Low-frequency ultrasound and high-frequency ultrasound are applied sequentially in each working cycle, with an interval between working cycles.
[0042] The ultrasonic treatment employed a power density of 250 W / L, using an alternating operation mode of 2 seconds of operation followed by 3 seconds of rest. Within each cycle, low-frequency ultrasound (20 kHz) was applied for the first second, followed by high-frequency ultrasound (80 kHz) for the next second. The isothermal treatment was conducted at 50°C for 25 minutes, with temperature control achieved via a circulating water bath. This dual-frequency alternation effectively combined fiber pore expansion with molecular chain rearrangement, enhancing the uniformity of structural modification. The material processed in this step proceeded directly to the next step without further drying or washing.
[0043] S6. Polysaccharide Pore Stabilization and Passivation: After ultrasonic treatment, homologous taro peel endogenous polysaccharides are added to the reaction system and stirred at a constant temperature.
[0044] The added endogenous polysaccharide and the taro polysaccharide used to prepare the eutectic solvent are homologous extracts with identical composition, and the amount added accounts for 1.5% of the total mass of the system; the constant temperature stirring temperature is 50℃, the rotation speed is 150r / min, and the processing time is 6.5min.
[0045] S7. Separation and drying sample preparation: Add deionized water to the reaction system for dilution, collect the precipitate by centrifugation, wash the precipitate until the eluent is neutral, and obtain the modified taro peel dietary fiber product after freeze drying.
[0046] The volume of deionized water added was 4 times the volume of the reaction system; the centrifugation speed was 4000 r / min and the centrifugation time was 10 min; the precipitate was washed repeatedly with deionized water 3 times until the eluent was neutral; the cold trap temperature for freeze drying was -45℃ and the drying time was 24 h.
[0047] Example 2: This example provides a method for modifying the dietary fiber in the peel of taro, and the specific process is as follows: S1. Raw material pretreatment: Take fresh taro peel, wash and remove impurities, and then process it through hot air drying, crushing and sieving to obtain taro peel dry powder.
[0048] Before drying, the taro skin is cut into 2cm pieces. The hot air drying temperature is 50℃ and the cross-sectional wind speed is 1.0m / s. After drying, the moisture content of the material is controlled at 9%. The crushing adopts a two-stage process of coarse crushing and fine crushing. After fine crushing, the sieve mesh size is 40 mesh.
[0049] S2. Steam flash explosion hole making: After adjusting the moisture content of taro peel powder, let it stand and soak, then perform steam explosion treatment, keep it at constant temperature and pressure, and then instantly release the pressure to normal pressure.
[0050] The adjusted material has a moisture content of 25% and a static soaking time of 15 minutes; the steam pressurization rate is 0.02 MPa / s; the constant temperature and pressure holding temperature is 110℃, the pressure is 0.15 MPa, and the holding time is 3 minutes; the total duration of instantaneous pressure relief is 0.1 seconds. The material processed in this step is directly introduced into the next step without further drying and washing.
[0051] S3, Acid Activation Treatment: After depressurization, the reaction system is kept in a closed state, and the residual heat of the material is used to maintain the system temperature for activation treatment. After activation, the activated material is discharged.
[0052] The soaking treatment is carried out at a temperature of 90℃ for 10 minutes. During the soaking process, the reaction system is maintained under a slight positive pressure, with a gauge pressure of 0.01 MPa. After soaking, the pressure is slowly released to atmospheric pressure before the material is discharged. This process utilizes the endogenous organic acids released from the material to gently loosen the surface structure of the fiber, increasing the number of active reaction sites. The activated material processed in this step is directly introduced into the next step without drying or washing.
[0053] S4. Solvent intercalation and deconstruction: The activated material is added to a pre-prepared endogenous eutectic solvent, the mass-volume ratio of the liquid is controlled, and the mixture is stirred at a constant temperature.
[0054] The endogenous eutectic solvent was prepared using citric acid and taro polysaccharide extracted from taro peel as hydrogen bond donors and choline chloride as hydrogen bond acceptor. The molar ratio of citric acid, taro polysaccharide, and choline chloride was 1:0.4:0.2. The preparation process involved mixing the three components and stirring at a constant temperature of 75°C until a homogeneous and transparent liquid was formed. The mixture was then cooled to room temperature before use. In this embodiment, the taro polysaccharide was obtained from taro peel and prepared using hot water extraction and ethanol precipitation. It is a water-soluble plant polysaccharide, and its molar amount was calculated based on monosaccharide residue equivalents. The material-to-liquid mass-to-volume ratio was 1:15. The constant temperature stirring temperature was 50°C, the stirring speed was 180 r / min, and the processing time was 40 min. The entire process was conducted under light-protected conditions to reduce the oxidative loss of endogenous active components. The material and solvent system processed in this step were directly introduced into the next step without drying or washing.
[0055] S5. Ultrasonic structural reconstruction: The material processed in step S4, together with the solvent system, is placed in an ultrasonic field and ultrasonically treated under constant temperature conditions. The ultrasonic treatment adopts an alternating operation of low-frequency ultrasound and high-frequency ultrasound. Low-frequency ultrasound and high-frequency ultrasound are applied sequentially in each working cycle, with an interval between working cycles.
[0056] The ultrasonic treatment employed a power density of 200 W / L, using an alternating operation mode of 2 seconds of operation followed by 3 seconds of rest. Within each cycle, low-frequency ultrasound (20 kHz) was applied for the first second, followed by high-frequency ultrasound (80 kHz) for the next second. The isothermal treatment was conducted at 45°C for 20 minutes, with temperature control achieved using a circulating water bath. This dual-frequency alternation effectively combined fiber porosity expansion with molecular chain rearrangement, enhancing the uniformity of structural modification. The material processed in this step was directly introduced into the next step without further drying or washing.
[0057] S6. Polysaccharide Pore Stabilization and Passivation: After ultrasonic treatment, homologous taro peel endogenous polysaccharides are added to the reaction system and stirred at a constant temperature.
[0058] The added endogenous polysaccharide and the taro polysaccharide used to prepare the eutectic solvent are homologous extracts with identical composition, and the amount added accounts for 1% of the total mass of the system; the constant temperature stirring temperature is 48℃, the rotation speed is 120r / min, and the processing time is 5min.
[0059] S7. Separation and drying sample preparation: Add deionized water to the reaction system for dilution, collect the precipitate by centrifugation, wash the precipitate until the eluent is neutral, and obtain the modified taro peel dietary fiber product after freeze drying.
[0060] The volume of deionized water added was three times the volume of the reaction system; the centrifugation speed was 3500 r / min and the centrifugation time was 8 min; the precipitate was washed repeatedly with deionized water three times until the eluent was neutral; the cold trap temperature for freeze drying was -50℃ and the drying time was 20 h.
[0061] Example 3: This example provides a method for modifying the dietary fiber in the peel of taro, and the specific process is as follows: S1. Raw material pretreatment: Take fresh taro peel, wash and remove impurities, and then process it through hot air drying, crushing and sieving to obtain taro peel dry powder.
[0062] Before drying, the taro skin is cut into 5cm pieces. The hot air drying temperature is 60℃ and the cross-sectional wind speed is 2.0m / s. After drying, the moisture content of the material is controlled at 7%. The crushing process adopts a two-stage process of coarse crushing and fine crushing. After fine crushing, the sieve mesh size is 60 mesh.
[0063] S2. Steam flash explosion hole making: After adjusting the moisture content of taro peel powder, let it stand and soak, then perform steam explosion treatment, keep it at constant temperature and pressure, and then instantly release the pressure to normal pressure.
[0064] The adjusted material has a moisture content of 30% and a static soaking time of 25 minutes; the steam pressurization rate is 0.05 MPa / s; the constant temperature and pressure holding temperature is 120℃, the pressure is 0.20 MPa, and the holding time is 5 minutes; the total duration of instantaneous pressure relief is 0.5 seconds. The material processed in this step is directly introduced into the next step without further drying and washing.
[0065] S3, Acid Activation Treatment: After depressurization, the reaction system is kept in a closed state, and the residual heat of the material is used to maintain the system temperature for activation treatment. After activation, the activated material is discharged.
[0066] The annealing process involves a temperature of 100℃ and a treatment time of 15 minutes. During annealing, the reaction system is maintained under a slight positive pressure, with a gauge pressure of 0.03 MPa. After annealing, the pressure is slowly released to atmospheric pressure before the material is discharged. This process utilizes the endogenous organic acids released from the material to gently loosen the surface structure of the fibers, increasing the number of active reaction sites. The activated material processed in this step is not dried or washed and proceeds directly to the next step.
[0067] S4. Solvent intercalation and deconstruction: The activated material is added to a pre-prepared endogenous eutectic solvent, the mass-volume ratio of the liquid is controlled, and the mixture is stirred at a constant temperature.
[0068] The endogenous eutectic solvent was prepared using citric acid and taro polysaccharide extracted from taro peel as hydrogen bond donors and choline chloride as hydrogen bond acceptor. The molar ratio of citric acid, taro polysaccharide, and choline chloride was 1:0.6:0.4. The preparation process involved mixing the three components and stirring at a constant temperature of 85°C until a homogeneous and transparent liquid was formed. The mixture was then cooled to room temperature before use. In this embodiment, the taro polysaccharide was obtained from taro peel and prepared using hot water extraction and ethanol precipitation. It is a water-soluble plant polysaccharide, and its molar amount was calculated based on monosaccharide residue equivalents. The material-to-liquid mass-to-volume ratio was 1:20. The constant temperature stirring temperature was 60°C, the stirring speed was 220 r / min, and the processing time was 60 min. The entire process was conducted under light-protected conditions to reduce the oxidative loss of endogenous active components. The material and solvent system processed in this step were directly introduced into the next step without drying or washing.
[0069] S5. Ultrasonic structural reconstruction: The material processed in step S4, together with the solvent system, is placed in an ultrasonic field and ultrasonically treated under constant temperature conditions. The ultrasonic treatment adopts an alternating operation of low-frequency ultrasound and high-frequency ultrasound. Low-frequency ultrasound and high-frequency ultrasound are applied sequentially in each working cycle, with an interval between working cycles.
[0070] The ultrasonic treatment employed a power density of 300 W / L, using an alternating operation mode of 2 seconds of operation followed by 3 seconds of rest. Within each cycle, low-frequency ultrasound (20 kHz) was applied for the first second, followed by high-frequency ultrasound (80 kHz) for the next second. The isothermal treatment was conducted at 55°C for 30 minutes, with temperature control achieved via a circulating water bath. This dual-frequency alternation effectively combined fiber porosity expansion with molecular chain rearrangement, enhancing the uniformity of structural modification. The material processed in this step was directly introduced into the next step without further drying or washing.
[0071] S6. Polysaccharide Pore Stabilization and Passivation: After ultrasonic treatment, homologous taro peel endogenous polysaccharides are added to the reaction system and stirred at a constant temperature.
[0072] The added endogenous polysaccharide and the taro polysaccharide used to prepare the eutectic solvent are homologous extracts with identical composition, and the amount added accounts for 2% of the total mass of the system; the constant temperature stirring temperature is 52℃, the rotation speed is 180r / min, and the processing time is 8min.
[0073] S7. Separation and drying sample preparation: Add deionized water to the reaction system for dilution, collect the precipitate by centrifugation, wash the precipitate until the eluent is neutral, and obtain the modified taro peel dietary fiber product after freeze drying.
[0074] The volume of deionized water added was 5 times the volume of the reaction system; the centrifugation speed was 4500 r / min and the centrifugation time was 12 min; the precipitate was washed repeatedly with deionized water 4 times until the eluent was neutral; the freeze-drying cold trap temperature was -40℃ and the drying time was 28 h.
[0075] Comparative Example 1: The only difference between this comparative example and Example 1 is that in step S4, when preparing the eutectic solvent, the citric acid extracted from taro peel is replaced with an equimolar amount of purchased food-grade citric acid. The other raw material ratios, process steps and parameters are completely consistent with Example 1.
[0076] Comparative Example 2: The only difference between this comparative example and Example 1 is that the steam explosion treatment in step S2 adopts industry-standard high temperature and high pressure parameters, and the constant temperature and pressure insulation temperature is 180℃ and the pressure is 1.0MPa. The other raw material ratios, process steps and parameters are completely consistent with Example 1.
[0077] Comparative Example 3: The only difference between this comparative example and Example 1 is that the closed simmering activation treatment in step S3 is omitted, and the material is directly discharged into step S4 after the steam explosion and depressurization in step S2. The remaining raw material ratios, process steps and parameters are completely consistent with Example 1.
[0078] Comparative Example 4: The only difference between this comparative example and Example 1 is that the ultrasonic treatment in step S5 adopts a single 40kHz frequency, a continuous mode of working for 2 seconds and then pausing for 3 seconds, without alternating between low and high frequencies. The other raw material ratios, process steps and parameters are completely consistent with Example 1.
[0079] Comparative Example 5: The only difference between this comparative example and Example 1 is that the pore stabilization and passivation treatment in step S6 is omitted, and the separation and drying process in step S7 is directly entered after the ultrasonic treatment. The remaining raw material ratios, process steps and parameters are completely consistent with Example 1.
[0080] Comparative Example 6: The only difference between this comparative example and Example 1 is that it adopts the conventional exogenous eutectic solvent combined with single-frequency ultrasonic modification process in the art. Specifically, it uses commercially available citric acid and choline chloride to prepare an exogenous eutectic solvent in a molar ratio of 1:2, combined with conventional steam explosion pretreatment at 160°C and single-frequency ultrasonic treatment at 20kHz. It does not set up the internal acid quenching and pore passivation process. All basic parameters such as the total treatment time and material-liquid ratio are consistent with those of Example 1, and the other operating procedures are completely consistent with those of Example 1.
[0081] I. Water-holding capacity determination: The test was conducted according to the method in GB / T22224-2008 Determination of Dietary Fiber in Food. 0.5 g of each of the dietary fiber samples prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were accurately weighed and placed in 50 mL centrifuge tubes that had been pre-dried and kept at constant weight. 15 mL of deionized water was added to each centrifuge tube, and the tubes were shaken thoroughly for 1 min to ensure complete dispersion. The tubes were then allowed to stand at a constant temperature of 25°C for 30 min. Subsequently, the centrifuge tubes were placed in a centrifuge and centrifuged at 4000 r / min for 10 min. The supernatant was carefully poured off and discarded. The centrifuge tubes were then inverted on filter paper to drain for 5 min, and the total mass of the samples in the tubes was weighed. The water-holding capacity of each sample was calculated based on the difference between the dry weight and the wet weight after water absorption. Each group of samples was measured in parallel three times, and the final result was the average of the three parallel tests.
[0082] II. Oil-holding capacity determination: The test was conducted according to the method in GB / T22224-2008 Determination of Dietary Fiber in Food. 0.5 g of each of the dietary fiber samples prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were accurately weighed and placed in 50 mL centrifuge tubes that had been pre-dried and kept at constant weight. 10 mL of food-grade refined soybean oil was added to each centrifuge tube, and the tubes were shaken thoroughly for 1 min to ensure that the sample and oil were fully mixed and soaked. The tubes were then allowed to stand at a constant temperature of 25°C for 30 min. Subsequently, the centrifuge tubes were placed in a centrifuge and centrifuged at 4000 r / min for 10 min. The upper free oil layer was carefully poured off and discarded. The centrifuge tubes were then inverted on filter paper to drain for 10 min, and the total mass of the sample in the tubes was weighed. The oil-holding capacity of each sample was calculated based on the difference between the dry weight of the sample and the wet weight after oil absorption. Each group of samples was tested in parallel three times, and the final result was the average of the three parallel tests.
[0083] III. Determination of DPPH free radical scavenging rate: The test was conducted according to the method in GB / T39100-2020 "Determination of DPPH free radical scavenging capacity in health foods". 1.0 g of each of the dietary fiber samples prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were accurately weighed and placed in stoppered conical flasks. 20 mL of 80% ethanol solution was added to each flask, and the mixture was thoroughly shaken. The flasks were then placed in a constant temperature shaking device and extracted at 150 r / min for 2 hours at 25°C in the dark. After extraction, the mixture was transferred to centrifuge tubes and centrifuged at 4000 r / min. Centrifuge at 10 min for 10 min, collect the supernatant to obtain the test extract of each sample, take 2 mL of the test extract and add it to a test tube, then add 2 mL of 0.2 mmol / L DPPH ethanol solution, mix thoroughly and let stand at 25℃ in the dark for 30 min, use a UV-Vis spectrophotometer to measure the absorbance of the reaction system at a wavelength of 517 nm, and set up a blank control group and a solvent control group. Calculate the scavenging rate of DPPH free radicals of each sample according to the absorbance values of each group. Each group of samples was measured in parallel 3 times, and the final result was the average of the three parallel experiments.
[0084] Table 1: Test results of dietary fiber properties of modified taro peel in each example and comparative example
[0085] Note: The water-holding capacity and oil-holding capacity tests in this table were performed in accordance with GB / T22224-2008 Determination of Dietary Fiber in Food, with an ambient temperature of 25℃ and centrifugation parameters of 4000 r / min for 10 min; the DPPH free radical scavenging rate test was performed in accordance with GB / T39100-2020 Determination of DPPH Free Radical Scavenging Capacity in Health Food, with a measurement wavelength of 517 nm and a reaction temperature of 25℃; all data are the average of three parallel test results, and the relative error of the parallel tests was controlled within 5%.
[0086] As can be seen from Examples 1-3 and Comparative Example 1, and Table 1, using endogenous citric acid extracted from the raw materials to prepare a eutectic solvent can form a more compatible modified system with the fiber matrix compared to exogenously added citric acid. This improves the degree of fiber structure loosening while better preserving the endogenous active components of the raw materials, thus synergistically improving the physicochemical functions and biological activity of the product.
[0087] As can be seen from Examples 1-3 and Comparative Example 2, and Table 1, the pretreatment method of low-temperature and low-pressure steam flash explosion, compared with the conventional high-temperature and high-pressure explosion process in the industry, can significantly reduce the thermal degradation loss of heat-sensitive active components while achieving effective pore-forming and loosening of the fiber structure, thus achieving the dual goals of structural modification depth and natural activity retention.
[0088] As can be seen from Examples 1-3 and Comparative Example 3, and Table 1, the addition of a closed-loop endogenous acid quenching activation process after flash explosion can utilize the organic acid precipitated by the material itself to penetrate deep into the fiber cracks, further loosening the amorphous structure of the fiber, providing sufficient channels for the diffusion and intercalation of the subsequent modified medium, enhancing the modification effect of the subsequent process, and forming a significant synergistic effect with the pre-flash explosion step.
[0089] As can be seen from Examples 1-3 and Comparative Example 4, and Table 1, the alternating low-frequency and high-frequency ultrasonic treatment mode can achieve the dual effects of fiber pore expansion and molecular chain rearrangement simultaneously, compared with single-frequency ultrasonic treatment. It takes into account both structural loosening and network structure construction, and improves the physicochemical adsorption performance and active component immobilization effect of the fiber in a more balanced way.
[0090] As can be seen from Examples 1-3 and Comparative Example 5 and Table 1, the addition of an endogenous polysaccharide pore-stabilizing passivation process after ultrasonic treatment can terminate the reaction and form steric hindrance on the fiber pore surface, inhibiting the rearrangement and aggregation of fiber molecular chains and pore collapse during the drying process, maintaining the porous structure of the modified fiber for a long time, and ensuring the stability of the product's adsorption performance.
[0091] As can be seen from Examples 1-3 and Comparative Example 6, and Table 1, the endogenous synergistic modification process of this application, compared with the conventional modification scheme of exogenous eutectic solvent combined with single-frequency ultrasound in the field, can form a synergistic effect across the entire chain from pretreatment, deep modification to posttreatment, achieving significant performance improvement in both physicochemical function and biological activity, with outstanding overall technical advantages.
[0092] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A method for modifying dietary fiber in taro peel, characterized in that: Includes the following steps: S1. Raw material pretreatment: Take fresh taro peel, wash and remove impurities, and then process it through hot air drying, crushing and sieving to collect taro peel dry powder. S2. Steam flash explosion hole making: After adjusting the moisture content of taro peel powder, let it stand and soak, then steam explosion treatment, keep it at constant temperature and pressure, and then instantly release the pressure to normal pressure. S3, acid aging and activation treatment: After depressurization, the reaction system is kept in a closed state, and the residual heat of the material is used to maintain the system temperature for aging treatment. After aging, the activated material is discharged. S4. Solvent intercalation and deconstruction: The activated material is added to a pre-prepared endogenous eutectic solvent, the mass-volume ratio of the material and the mixture is controlled, and the mixture is stirred at a constant temperature. S5. Ultrasonic structural reconstruction: The material processed in step S4, together with the solvent system, is placed in an ultrasonic field and ultrasonically treated under constant temperature conditions. The ultrasonic treatment adopts a method of alternating low-frequency and high-frequency ultrasound. Low-frequency ultrasound and high-frequency ultrasound are applied sequentially in each working cycle, with an interval between working cycles. S6. Polysaccharide pore-stabilizing passivation: After ultrasonic treatment, homologous taro peel endogenous polysaccharide is added to the reaction system and stirred at a constant temperature. S7. Separation and drying sample preparation: Add deionized water to the reaction system for dilution, collect the precipitate by centrifugation, wash the precipitate until the eluent is neutral, and obtain the modified taro peel dietary fiber product after freeze drying.
2. The method for modifying dietary fiber in taro peel according to claim 1, characterized in that: In step S1, the temperature of the hot air drying is 50 to 60°C, the cross-sectional wind speed is 1.0 to 2.0 m / s, the taro skin is cut into small pieces of 2 to 5 cm before drying, and the moisture content of the material after drying is less than 10%; the crushing adopts a two-stage process of coarse crushing and fine crushing, and the sieve mesh number is 40 to 60 mesh.
3. The method for modifying dietary fiber in taro peel according to claim 1, characterized in that: In step S2, the moisture content is 25% to 30%, and the static soaking time is 15 to 25 minutes; the constant temperature and pressure insulation temperature is 110 to 120°C, the pressure is 0.15 to 0.20 MPa, and the insulation time is 3 to 5 minutes; the steam pressure rise rate is 0.02 to 0.05 MPa / s, and the total duration of instantaneous pressure relief is 0.1 to 0.5 seconds.
4. The method for modifying dietary fiber in taro peel according to claim 1, characterized in that: In step S3, the temperature of the simmering treatment is 90 to 100°C and the treatment time is 10 to 15 minutes. During the simmering process, the reaction system is maintained under a slightly positive pressure, with a gauge pressure of 0.01 to 0.03 MPa. After the simmering is completed, the pressure is first slowly released to atmospheric pressure before the material is discharged.
5. The method for modifying dietary fiber in taro peel according to claim 1, characterized in that: In step S4, the endogenous eutectic solvent is prepared using citric acid and taro polysaccharide extracted from taro peel as hydrogen bond donors and choline chloride as hydrogen bond acceptor. The molar ratio of citric acid, taro polysaccharide and choline chloride is 1:0.4 to 0.6:0.2 to 0.
4. The preparation process involves mixing the three components and stirring at a constant temperature of 75 to 85°C until a homogeneous and transparent liquid is formed. The mixture is then cooled to room temperature before use.
6. The method for modifying dietary fiber in taro peel according to claim 1, characterized in that: In step S4, the mass-to-volume ratio of the material to the liquid is 1:15 to 1:20, the temperature of the constant-temperature stirring is 50 to 60°C, the rotation speed is 180 to 220 r / min, and the processing time is 40 to 60 min; the entire process is carried out under light-protected conditions.
7. The method for modifying dietary fiber in taro peel according to claim 1, characterized in that: In step S5, the power density of the ultrasonic treatment is 200 to 300 W / L, and an alternating operation mode of 2 seconds working and 3 seconds intermittent is adopted; in each working cycle, low-frequency ultrasound with a frequency of 20 kHz is applied in the first 1 second, and high-frequency ultrasound with a frequency of 80 kHz is applied in the last 1 second; the temperature of the constant temperature treatment is 45 to 55℃, and the treatment time is 20 to 30 minutes; a circulating water bath is used for temperature control during the ultrasonic treatment.
8. The method for modifying dietary fiber in taro peel according to claim 1, characterized in that: In step S6, the added endogenous polysaccharide and the taro polysaccharide used to prepare the eutectic solvent are homologous extraction components, and the amount added accounts for 1% to 2% of the total mass of the system; The temperature for constant temperature stirring is 48 to 52°C, the speed is 120 to 180 r / min, and the processing time is 5 to 8 min.
9. The method for modifying dietary fiber in taro peel according to claim 1, characterized in that: In step S7, the volume of deionized water added is 3 to 5 times the volume of the reaction system; the centrifugation speed is 3500 to 4500 r / min, and the centrifugation time is 8 to 12 min; the cold trap temperature for freeze drying is -50 to -40℃, and the drying time is 20 to 28 h.
10. The method for modifying dietary fiber in taro peel according to claim 1, characterized in that: In steps S2 to S6, between two adjacent steps, the material obtained in the previous step is used directly as the feed for the next step without being dried or washed.
